Pengaruh School Well Being terhadap Prestasi Belajar Siswa di SMA Negeri 3 Bukittinggi - Rahayu, Dini; Afrida, Yeni; Arjoni, Arjoni; Hartati, Sri (Lembaga Yasin AlSys, 2024)
This research was motivated by the condition of condition of student well-being (school well-being) at SMA Negeri 3 Bukittinggi which includes four aspects includes four aspects: school facilities (having), student self-fulfillment (being), social relationships (loving), and health (health). The research aims to to determine the effect and level of influence of school well-being on student achievement. student learning achievement. Using an associative type quantitative approach, this research This study involved 149 respondents who were selected by proportional random sampling. The research instrument was a questionnaire, and data analysis used simple regression. regression. The results showed the average score of students' school well-being score of 126 (high) with a percentage of 84%, and learning achievement in the competent category (100%). competent category (100%). Hypothesis testing shows school well-being has a significant effect on learning achievement with a significance value of 0.000 (<0.05) and Fcount (16.461) > Ftable (3.91). The effect of school well-being on learning achievement is 10.1%, so it can be concluded that school well-being plays an important role in improving learning achievement. that student well-being plays an important role in improving learning achievement.